Incidence and clinico-demographic characteristics of neonatal meningitis in clinically suspected sepsis: an observational study - Jadhav, Rupali; Bhaisara, Baraturam; Bhatawdekar, Anjali B (International Journal of Contemporary Pediatrics, 2019)
Background: Authors objective was to study the incidence and risk factors for meningitis in neonates with clinical suspicion of sepsis in Neonatal Intensive Care Unit (NICU) of tertiary care hospital of Mumbai, India. Methods: This descriptive observational study enrolled Consecutive 92 patients of either sex with suspected neonatal sepsis admitted in NICU of Tertiary Care Hospital. All neonates admitted to NICU with clinical suspicion of sepsis or developing signs of sepsis during NICU stay were included in study. Exclusion criteria were 1.Neonates with hemodynamic instability 2.major congenital malformations 3.contraindication or no willingness for Lumber puncture (LP ) 4.neonates who have received intravenous antibiotics for more than 24 hours elsewhere. Standard data collection form was used to collect all demographic data and clinical characteristics of neonates. Results: Incidence of meningitis in study population was 7.6%. Cases of meningitis in study population had mean birth weight 1.91 kg, 71.43% were preterm, 57.14% vaginaly delivered, 42.86% by LSCS, Premature rupture of membrane (PROM) observed in 28.57% cases. Meconium stained liquor in 42.86% cases and foul smelling liquor in 28.57% cases observed. 42.86% cases required resuscitation and 28.57% received surfactant therapy. Poor feeding (100%), lethargy (85.71%), weak cry (85.71%) and tachypnea (50.58%). Retractions (85.71%), Grunting (57.14%) and Nasal flaring (42.86%) were clinical presentation. Lab findings in a case of meningitis: mean Hemoglobin (Hb) 15.22 gm%, Leukopenia (28.57%), Leukocytosis 28.57%, Absolute Neutrophil count (ANC) <1800 (28.57%), Thrombocytopenia 42.85%, blood culture positive (28.57%) hypoglycemia (28.57%), CSF white cell count (124.57cells/ml.), mean CSF protein level (60 mg/dl.) Mean CSF glucose level (40.86 mg/dl.) CSF culture was positive in two cases of meningitis. Conclusions: Authors study highlights the diagnostic utility of routine lumbar puncture in neonates with clinically suspected sepsis.